LAA occlusion is effective and safe in very high-risk atrial fibrillation patients with prior stroke: results from the multicentre German LAARGE registry - Ansari, Uzair; Brachmann, Johannes; Lewalter, Thorsten; Zeymer, Uwe; Sievert, Horst; Ledwoch, Jakob; Geist, Volker; Hochadel, Matthias; Schneider, Steffen; Senges, Jochen; Akın, Ibrahim; Fastner, Christian (Clinical research in cardiology, 2024)
Interventional left atrial appendage occlusion (LAAO) mitigates the risk of thromboembolic events in nonvalvular atrial fibrillation (AF) patients with contraindication for long-term oral anticoagulation (OAC). Patients with prior stroke have a relevantly increased risk of recurrent stroke, so the effectiveness of LAAO could be reduced in this specific very high-risk patient group.
Online veröffentlicht: 31. Januar 2024
Gesehen am 25.11.2024